2013
DOI: 10.3758/s13423-013-0400-9
|View full text |Cite
|
Sign up to set email alerts
|

Substituting objects from consciousness: A review of object substitution masking

Abstract: Object substitution masking (OSM) occurs when a sparse (e.g., four-dot), temporally trailing mask obscures the visibility of a briefly presented target. Here, we review theories of OSM: those that propose that OSM reflects the interplay between feedforward and feedback/reentrant neural processes, those that predict that feedforward processing alone gives rise to the phenomenon, and theories that focus on cognitive explanations, such as object updating. We discuss how each of these theories accommodates key fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 122 publications
(197 reference statements)
0
49
0
Order By: Relevance
“…The implications of these findings are considerable. If ceiling effects have been driving the interaction between attention and masking magnitude, then the role of attention is OSM is likely to be different to that previously presumed in the numerous models of OSM that have been developed (Goodhew et al, 2013). Thus, this will impact upon our conceptualization of OSM and the mechanisms hypothesised to underlie the phenomenon and, indeed, other forms of masking.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The implications of these findings are considerable. If ceiling effects have been driving the interaction between attention and masking magnitude, then the role of attention is OSM is likely to be different to that previously presumed in the numerous models of OSM that have been developed (Goodhew et al, 2013). Thus, this will impact upon our conceptualization of OSM and the mechanisms hypothesised to underlie the phenomenon and, indeed, other forms of masking.…”
Section: Introductionmentioning
confidence: 93%
“…However, if the mask offset is delayed relative to that for the target, visibility of the target is reduced. OSM is thought to reflect the dynamics of reentrant neural processing (Fahrenfort, Scholte, & Lamme, 2007a;Fahrenfort, Scholte, & Lamme, 2007b;Fahrenfort, Scholte, & Lamme, 2005;Lamme & Roelfsema, 2000;Lamme, Super, & Spekreijse, 1998), where feedforward and feedback neural signals interact to resolve incongruent perceptual hypotheses at different levels of information processing (Di Lollo, Enns, & Rensink, 2000;Dux, Visser, Goodhew, & Lipp, 2010;Goodhew, Pratt, Dux, & Ferber, 2013;Jannati, Spalek, & Di Lollo, 2013). Specifically, visual information is fed from primary visual cortex to higher-level regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used objectsubstitution masking (OSM) (Enns & Di Lollo, 1997), in which the visibility of a target item is impaired by a sparse four-dot mask that has a delayed offset from the target (for a review, see Goodhew et al, 2013). Harrison and colleagues (2015) found that the precision of a visual representation was affected by the presence and timing of a mask.…”
mentioning
confidence: 99%
“…According to one prominent theory, OSM occurs due to a conflict between the target object and the mask at different stages of visual processing, reflecting re-entrant processing between primary visual cortex (V1), other areas of occipital cortex and higher cortical areas in the temporal and parietal lobes (Di Lollo, Enns, & Rensink, 2000;Dux, Visser, Goodhew, & Lipp, 2010). Another account, the object updating hypothesis, suggests that OSM is caused by a failure in individuation of the target and the mask (Lleras & Moore, 2003;Pilling & Gellatly, 2010), possibly due to limitations in the temporal resolution of visual encoding (Goodhew, Pratt, & Dux, 2013). Carlson, Rauschenberger, and Verstraten (2007) found that neural responses to repeated targets subject to OSM reflected adaptation in V1 but not lateral occipital cortex, suggesting the neural representation of the masked target object was reduced, if not completely suppressed, in ventral occipital cortex.…”
Section: Introductionmentioning
confidence: 99%